1992
DOI: 10.1002/1097-0142(19920401)69:7<1818::aid-cncr2820690726>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Flow cytometry method for the analysis of membrane-associated human chorionic gonadotropin, its subunits, and fragments on human cancer cells

Abstract: A quantitative flow cytometry method for the analysis of membrane‐associated human chorionic gonadotropin (hCG), its subunits, and fragments on human cancer cells was developed using a double‐antibody reaction; a flow cytometer with a 2‐W argon laser, standard settings, and filters for fluorescein isothiocyanate use; commercially available software; and the ectopic hCG producer CCL 2 HeLa cells from the American Type Culture Collection (ATCC) as a cell control to standardize the reagents and for overall qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…In the years that followed Acevedo and Krichevsky [126] and Regelson [127] used cancer membrane flow cytometry methods to show that all advanced cancers produced an hCG free ß-subunit variant. An investigation into hCG degradation at that time showed that hCG free ß-subunit (circulating 1/2-life 0.72 h) is removed from the circulation much more rapidly than hCG (circulating 1/2-life 36 h) [128].…”
Section: Introductionmentioning
confidence: 99%
“…In the years that followed Acevedo and Krichevsky [126] and Regelson [127] used cancer membrane flow cytometry methods to show that all advanced cancers produced an hCG free ß-subunit variant. An investigation into hCG degradation at that time showed that hCG free ß-subunit (circulating 1/2-life 0.72 h) is removed from the circulation much more rapidly than hCG (circulating 1/2-life 36 h) [128].…”
Section: Introductionmentioning
confidence: 99%
“…Three years later, using quantitative analytical flow cytometry and a battery of monoclonal antibodies directed to different epitopes of the hCG molecule, Acevedo and his associates demonstrated the expression of membrane‐associated hCG, its subunits and fragments by live cancer cells of every type and origin (10–12). Using the same methodology, and the nude mouse model, Acevedo and Hartsock pointed out that there was a direct in vivo correlation between human cancer cells that metastasize spontaneously in nude mice, and the expression of membrane‐associated complete hCGβ.…”
Section: Introductionmentioning
confidence: 99%
“…Since all the normal cells from our immune system, macrophages, NK cells and B cells, express in their membranes a “normal” negative charge, the high negative charge of hCG and its subunits demonstrated to be present in the cell membranes of embryonic and fetal cells, in sperm cells in every stage of development (Figures 3,4) (60–62), and in all cancer cells irrespective of type or origin as membrane‐associated hCG (10–13), make all these cells immunologically inert . The cells from the immune system cannot approach, cannot touch, since negative charges repel.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations